1993
DOI: 10.1021/bp00022a004
|View full text |Cite
|
Sign up to set email alerts
|

A Computer Model for Intracellular pH Regulation in Chinese Hamster Ovary Cells

Abstract: A single-cell model for Chinese hamster ovary (CHO) cells has been extended to study the regulation of intracellular pH. This model provides for the first time a direct mechanistic linkage between intracellular pH control and cellular metabolism. Among the known mechanisms that regulate and disturb pHi, the Na/H antiport, effect of lactate and ammonia, proton leakage, and external pH have been included in the model. The ability of the model to predict both steady-state and transient pHi has been tested against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…The recovery of pH in could be a result of metabolic consumption of intracellular fatty acids and/or a proton leak caused by various mechanisms (48). However, because the decrease in unesterified oleate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of pH in could be a result of metabolic consumption of intracellular fatty acids and/or a proton leak caused by various mechanisms (48). However, because the decrease in unesterified oleate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a complete medium exchange was performed on days 5.8 and 7.7 for both the AHFBR and the slabs. The intracellular pH of CHO cells should not be affected at pH 6.8 31 but their growth rate may have been reduced during the last day of culture at pH \ 7.0. 32 CHO cells in alginate slabs grew exponentially at least until Day 7.8, just before harvest on Day 8.3 ( Figure 6A).…”
Section: Ahfbr Immobilized Culture Of Cho Cellsmentioning
confidence: 99%
“…This might induce a cytoplasmic alkalanization (Frelin et al, 1988). Ammonium ions might acidify the cell cytoplasm, by a mechanism called “proton shuttle” (McQueen and Bailey, 1990b; Wu et al, 1993): the ammonium ions, having an extracellular origin when one is studying the effect of this component and having an intracellular origin under normal culture conditions, can penetrate into the cells. In the last case, the ammonium ions issued from the cell metabolism are evacuated from the cells under the form NH 3 by passive diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…If this charge is too important compared to the evacuation of protons from the cell, pH i will decrease. Some studies reported already results where one or more of the above‐mentioned culture variables were studied in relation to pH i and where their effect on cell and culture behavior could indeed be associated with an effect on pH i (McQueen and Bailey, 1991; Ozturk et al, 1992; Wu et al, 1993). They dealt however with very short‐term experiments on cells resuspended in buffers, while our work aims at studying cells in normal real culture conditions for longer exposure times, since we have evidence to believe that such measurements reflect better the real cell behavior.…”
Section: Introductionmentioning
confidence: 99%